2021
DOI: 10.1128/msystems.00626-21
|View full text |Cite
|
Sign up to set email alerts
|

Accessory Genomic Epidemiology of Cocirculating Acinetobacter baumannii Clones

Abstract: Whole-genome sequencing for epidemiological investigations (genomic epidemiology) has been of paramount importance to understand the transmission dynamics of many bacterial (and nonbacterial) pathogens. Commonly, variation in the core genome, single nucleotide polymorphisms (SNPs), is employed to carry out genomic epidemiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 48 publications
1
19
1
Order By: Relevance
“…This strategy has been very useful to appraise the dissemination of bacterial pathogens over different scales, from global to national and even in local settings. [4][5][6] However, core genomic epidemiology neglects an important amount of the phylogenetic information contained in the accessory genome, which are regions of the genome present in some but not all of the isolates considered. In bacterial genomic epidemiology the accessory genome is commonly discarded as it does not follow vertical transmission; however, we now have a much better understanding of this part of the genome and a better framework to integrate it with the phylogenetic signals residing the in the core genome.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This strategy has been very useful to appraise the dissemination of bacterial pathogens over different scales, from global to national and even in local settings. [4][5][6] However, core genomic epidemiology neglects an important amount of the phylogenetic information contained in the accessory genome, which are regions of the genome present in some but not all of the isolates considered. In bacterial genomic epidemiology the accessory genome is commonly discarded as it does not follow vertical transmission; however, we now have a much better understanding of this part of the genome and a better framework to integrate it with the phylogenetic signals residing the in the core genome.…”
mentioning
confidence: 99%
“…In a 2021 study, which analysed the dissemination of A baumannii within a hospital, the potential for using the accessory genome to conduct genomic epidemiology was shown. 6 To fully understand the transmission of several co-circulating lineages of A baumannii, Mateo-Estrada and colleagues 6 made use of gene content variation within the accessory genome in addition to using classical core genomic epidemiology. Notably, the variation in the accessory genome was of paramount importance to establish the high rate of transmission across the different wards in the hospital.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently shown that different lineages of A. baumannii can co-exist in individual hospital settings [22, 31].…”
Section: Discussionmentioning
confidence: 99%
“…We also run a maximum-likelihood (ML) non-recombinant core phylogeny as we have done previously in a genomic epidemiology study of A. baumannii [22]. First, we defined the core genes and excluded all the core genes that had recombination signals (recombination was detected as stated below).…”
Section: Methodsmentioning
confidence: 99%